Understanding Transformer Architecture and Its Impact on Large Language Models in Healthcare - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Explore transformer architecture and its role in powering large language models that assist clinical documentation, diagnosis, and multimodal medical analysis.
Keywords: transformer architecture; large language models; AI in healthcare; clinical documentation; medical AI limitations